2011
DOI: 10.1159/000329547
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Glomerular Filtration Rate in Obese Patients: Pitfalls and Potential Consequences on Drug Therapy

Abstract: Epidemiological studies have shown that obesity is associated with chronic kidney disease and end stage renal disease. These studies have used creatinine derived equations to estimate glomerular filtration rate (GFR) and have indexed GFR to body surface area (BSA). However, the use of equations using creatinine as a surrogate marker of glomerular filtration and the indexation of GFR for BSA can be questioned in the obese population. First, these equations lack precision when they are compared to gold standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…The CG equation has been used for several decades and is still part of the guidance from the FDA and the EMA in pharmacokinetic studies in the setting of renal impairment . Its accuracy for estimating GFR is, however, not optimal in obese patients, as expected by the bias induced by the ABW in the equation . Pharmacologists justify the use of the CG equation by different arguments.…”
Section: Discussionmentioning
confidence: 99%
“…The CG equation has been used for several decades and is still part of the guidance from the FDA and the EMA in pharmacokinetic studies in the setting of renal impairment . Its accuracy for estimating GFR is, however, not optimal in obese patients, as expected by the bias induced by the ABW in the equation . Pharmacologists justify the use of the CG equation by different arguments.…”
Section: Discussionmentioning
confidence: 99%
“…In morbidly obese patients who presented with proteinuria, one study reported focal glomerular sclerosis, diabetic nephropathy, or both (42). In addition, estimates of the creatinine clearance from standard formulas tend to be inaccurate in obese patients (43)(44)(45). Even though obesity-associated renal damage may be unpredictable, the available evidence indicates that it is best to use LBW in the Cockroft-Gault formula for estimation of creatinine clearance in obese patients (44,46).…”
Section: Physiological Changes Associated With Obesitymentioning
confidence: 99%
“…The authors suggest that the poor performance of these equations may be attributed to high obesity rates typically found in patients with Type 2 diabetes. In fact, the use of creatinine‐based equations as a surrogate marker of GFR and the indexation of GFR for body surface area have been questioned in the obese population [3–5]. These equations lack precision when compared with gold standard GFR measurements in this group of patients [3,5].…”
Section: Glomerular Filtration Rate (Gfr) Bias and Accuracy (P30) Omentioning
confidence: 99%
“…In fact, the use of creatinine‐based equations as a surrogate marker of GFR and the indexation of GFR for body surface area have been questioned in the obese population [3–5]. These equations lack precision when compared with gold standard GFR measurements in this group of patients [3,5]. In addition, the indexation of GFR for 1.73 m 2 of body surface area leads to a systematic underestimation of GFR compared with absolute GFR in obese patients who have body surface areas that usually exceed 1.73 m 2 [3].…”
Section: Glomerular Filtration Rate (Gfr) Bias and Accuracy (P30) Omentioning
confidence: 99%
See 1 more Smart Citation